THE EFFECTIVENESS OF TWO STAY TWO STRAY IN TEACHING READING COMPREHENSION - Fathurrahman Imran (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2015)
This research was aimed: to find out significant effect of Two Stay Two Stray in Teaching Reading Comprehension at the second year Students of MTs Hidayatussibyan NW Sengkerang in academic year 2013/2014. The kind of this research was quantitative research. The population of this research was the second grade students that consist of 28 students. The instrument of collecting data used test which was 50 multiple choice items. In this research, the researcher gave a treatment and prepared a test in form of multiple choices to look for the effect of Two Stay Two Stray in Teaching Reading Comprehension. The result of the data analysis indicated that the grade students obtained high score on the post test. It means that, the Two Stay Two Stray gave a significant effect in students’ reading comprehension. It was proven by the lowest and highest score in pre-test and post-test, they were 20 and 58 and post-test were 32 and 80. Thus, the result of alternative hypothesis was accepted. It was provable that ttest was higher than ttable, which was the value of ttest was 4.875 and ttable 27 in significance level of 0.05% was 2.052.